Art and psychoanalysis in the treatment of psychosis : proximity and differences between the proposal of Nise da Silveira and Henry Bauchau - Messias, Caio Leal (Tematicas, 2020)
In 1982, the Belgian writer, psychoanalyst and playwright Henry Bauchau Bauchau gives a series of lectures on Art and Psychoanalysis at the University Paris VII. His book L’enfant bleu tells the story of Orion, a young psychotic who, with the help of psychoanalyst Véronique, discovers in art a way to deal with his symptoms. The artist Lionel, a former patient, inspired the book. There are proximities between the works of Véronique/Bauchau and psychiatrist Nise of Silveira in Brazil in the 1940s. They both fear the iatrogenic effects of the asylum model and the chemical straitjacket. In both cases, an alternative form of “cure” is sought, a treatment by word and art. In this treatment it is more important to “care for oneself”, the strengthening of the “I” and finding a place in the world than the search for an “absolute normality”. This article explores proximities and differences between the proposals.